Examining the Structure of Negative Affect Regulation and Its Association With Hedonic and Psychological Wellbeing - Puente-Martínez, Alicia; Páez, Darío; Ubillos-Landa, Silvia; Da Costa-Dutra, Silvia (Frontiers in Psychology, 2018)
The present study examines the structure of negative affect regulation strategies by confirmatory factor analysis. A total of 264 students (n= 187 women, 65 men) (M = 24 years; SD = 9.32) took part in this study. Results show a good fit indices for a three facets model: 1. modification of situation (problem-directed action, seeking emotional and instrumental social support, psychological abandonment and social isolation); 2. attentional deployment and cognitive change (distraction, acceptance, gratitude, rumination, reappraisal, spirituality and social comparison); and 3. response modification (suppression, active and passive physiological, humor & warmth, venting, confrontation, and regulated emotional expression). The scale validity is confirmed through correlations between the expanded of Mood Affect Regulation Scale expanded dimensions including dimensions of dispositional reappraisal and suppression, and hedonic and psychological well-being. Participants report an adaptive profile with high psychological well-being, even if they report low positive affect, suggesting a greater relevance of eudaimonic than hedonic well-being for affect regulation.